The 100 Most-cited Articles in Abdominoplasty: A Bibliometric Analysis. Issue 3 (26th March 2021) - Khajuria, Ankur; Charles, Walton N.; Dutt, Atul; Hoyos, Alfredo
Abstract : Background: Abdominoplasty is one of the most common aesthetic procedures performed globally. Research in this field is evolving, with recent emphasis on evidence-based surgery optimizing informed consent. This bibliometric analysis aimed to characterize emerging research trends and to assess the methodological quality of the highest impact abdominoplasty research. Methods: The 100 most-cited articles in abdominoplasty were identified on Web of Science, across all available journals and years (1950–2019). Study details, including the citation count, main subject, and outcome measures, were extracted from each article by 2 independent reviewers. The level of evidence of each study was also assessed. Results: The 100 most-cited articles in abdominoplasty were cited by a total of 2545 articles. Citations per article ranged from 206 to 34 (mean 65). Overall, 50 articles were assessed to be level of evidence 3, which is representative of the large number of cohort studies (n = 59) on the list. Similar numbers achieved levels 2, 4, and 5 (n = 16, 20, and 14), though none reached level 1. The main subject was operative technique in 50 articles, followed by outcomes in 34 articles. Only 7 articles utilized objective cosmetic outcome measures. Patient-reported outcome measures were employed in 25 articles, though only 5 incorporated validated questionnaires. Conclusions: The most-cited research in abdominoplasty largely comprised low-to-moderate quality studies, with no article achieving the highest level of evidence. Contemporary high-quality evidence incorporating validated outcome measures is crucial to enhance shared decision-making, particularly in aesthetic procedures.